The Nature of Legal Contract for Virtual Media in Iraqi Legislation - Ali, Riyad Huseen (International Journal of Psychosocial Rehabilitation, 2020)
Scientific and technological knowledge is one of the most important conquests of the world today, as it is the main source of knowledge, development and progress in this life in different fields. Today, the world is witnessing a tremendous growth in various sciences and fields, including the information and communication revolution, the intangible digital virtual environment, which is different to the traditional physical environment known. One of the conclusions of this hypothetical cognitive progress, especially in the field of information communication, is the Global Information Network, which has many and varied uses, most notably the massive transmission of information and massive international commercial contracting. The information started to reach the far north of the earth to the far south, and from the far west to the Far East, thanks to the development of the means of information and communication technology [1-3]. The day when a global information revolution is comparable (industrial revolution), it even superior, because it has reduced all geographical boundaries with a short time and cost, which is called a super-fast information revolution, this is why the current era has been called high-speed information age and has demonstrated new types of business known as e-business. In this research, I will address the study of the electronic contract, which is the most important means of electronic commerce, as this contract has characteristics that are not available in contracts concluded by conventional means, as it is built in a virtual, non-physical environment and across global communications networks that do not recognize the geographic boundaries of countries, and is often edited on non-paper supports stored within information systems [4].